Penggunaan Kayu Reklamasi untuk Furniture - Nangoy, Oktavianus Marti (Humaniora, 2010)
Our everyday activities cannot be separated from the use of furniture, especially the indoor activities. We use a bed to sleep, sitting in a chair, or other activities. Various designs of furniture made to adapt human activities. But have we ever thought about the materials used for the furniture? Wood is a common material used in furniture. This article is made to encourage designers being responsible towards living environment. They are charged to love nature and realize that their participation in defining natural preservation is huge. Design is the starter of eco living and all designed stuffs and then well produced from choosing material until its effects in the future, because everything will directly affect ourselves and environment.